Feedback Practices in B.Ed TESL Program in Higher Education - Chan Yuen Fook; Aisyah Nazamuddin (UiTM Publisher, 2014)
This study investigated the perceptions on feedback practices in the Bachelor of Education in Teaching of English as a Second Language (B.Ed TESL) program at the Faculty of Education, Universiti Teknologi MARA (UiTM), Shah Alam. It investigated the quantity, timing, quality and utilisation of feedback provided to the students in the program. A mixed method approach was employed whereby questionnaire and semi-structured interview questions were utilized. A total of 105 participants were selected through cluster sampling to answer the questionnaire. Besides that, four students and four lecturers were selected to provide insights for the interviews. The findings portrayed a moderate level of feedback practices among the undergraduate students in B.Ed TESL program. Overall, the study implies the importance of providing feedback to undergraduates in teaching and learning in higher education.